Synthesis and magnetic properties of polycrystalline Co-doped ZnO - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline Zn1-xCoxO powders have been synthesized by a glycine-nitrate (GNP) and modified GNP methods. Ferromagnetism at room temperature and above is observed for the powder samples synthesized by GNP method. The saturation magnetization value at 300 K is obtained as 0.08 and 0.28 emu/g (at 1 T), respectively, for x = 0.05 and 0.1. Ferromagnetic transition occurs at 740 K and 770 K for the respective samples, which is much larger than that the reported in the literature for thin film samples. On the other hand, no ferromagnetism was observed, down to 10 K, for the compounds synthesized by the modified GNP method.

Size-dependent magnetic properties of nanocrystalline yttrium iron garnet powders - Rajendran, M.; Deka, Sasanka; Joy, Pattayil Alias; Bhattacharya, Asish K. (Journal of Magnetism and Magnetic Materials, 2006)
Yttrium iron garnet (YIG) powders with particle sizes of 9, 14, 25 and 60 nm have been synthesised and their magnetic properties have been studied as a function of particle size and temperature. The particles with sizes of 9 and 14 nm exhibited superparamagnetism. The blocking temperature (T-B) decreased with decreasing particle size, whereas the anisotropy constant (K) increased. The saturation magnetisation (M-s) decreased with decreasing particle size. These variations are attributed to large surface-to-volume ratios in nanoparticles where the surface moments are predominant. (c) 2005 Published by Elsevier B.V.
Keywords: anisotropy constant; Magnetism; Nanoparticles; Superparamagnetism; YIG

Synthesis and magnetic properties of Mn doped ZnO nanowires - Deka, Sasanka; Joy, Pattayil Alias (Solid State Communications, 2007)
Mn doped ZnO nanowires have been synthesized using a simple autocombustion method. The as-synthesized Mn doped ZnO nanowires were characterized by X-ray diffraction and transmission electron microscopy. An increase in the hexagonal lattice parameters of ZnO is observed on increasing the Mn concentration. Optical absorption studies show an increment in the band gap with increasing Mn content, and also give evidence for the presence of Mn2+ ions in tetrahedral sites. All Zn1-xMnxO (0 <= x <= 0.25) samples are paramagnetic at room temperature. However, a large increase in the magnetization is observed below 50 K. This behavior, along with the negative value of the Weiss constant obtained from the linear fit to the susceptibility data below room temperature, indicate ferrimagnetic behavior. The origin of ferrimagnetism is likely to be either the intrinsic characteristics of the Mn doped samples, or due to some spinel-type impurity phases present in the samples that could not be detected. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; diluted magnetic semiconductor; magnetic properties; Mn doped ZnO

Studies on ZnO based diluted magnetic semiconductors - Deka, Sasanka; Joy, P. A. (TMS 2008 Annual Meeting Supplemental Proceedings, 2008)
The observation of ferromagnetism in the transition metal (TM) doped wide band gap nonmagnetic semiconductor ZnO opened up a new area of research because of the potential applications in spintronics devices. These ZnO based diluted magnetic semiconductors (DMS) combine their transport and optical properties with magnetism. We have carried out synthesis and studies on the magnetic and optical properties on TM doped ZnO powders in nanocrystalline form. Our studies give evidence for the origin of ferromagnetism as extrinsic due to the presence of metal nanoclusters as secondary phases in the Co and Ni doped ZnO systems although the optical and electronic structure studies indicate the incorporation of divalent metal ions inside the ZnO crystal lattice.

Superparamagnetic nanocrystalline ZnFe2O4 with a very high curie temperature - Deka, Sasanka; Joy, Pattayil Alias (Journal of Nanoscience and Nanotechnology, 2008)
Studies on the magnetic properties of nanocrystalline ZnFe2O4 synthesized by an autocombustion method are reported. Superparamagnetic behavior is observed for the nanocrystalline materials with particle sizes of 8 nm and 17 nm, with superparamagnetic blocking temperatures of 65 K and 75 K, respectively. Magnetic hysteresis with very large coercivities of 533 Oe and 325 Oe, respectively, are observed at 12 K. Studies on the temperature variation of the magnetization above room temperature indicate that the Curie temperature is as high as similar to 800 K when compared to the paramagnetic nature of bulk zinc ferrite at room temperature.
Keywords: Curie temperature; Nanocrystalline; Superparamagnetism; Zinc Ferrite

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.